Light response of gametophyte in Adiantum flabellulatum: transcriptome analysis and identification of key genes and pathways - Cai, Zeping; Wang, Xiaochen; Xie, Zhenyu; Wen, Zhenyi; Yu, Xudong; Xu, Shitao; Su, Xinyu; Luo, Jiajia (Frontiers in Plant Science, 2023)
Light serves not only as a signaling cue perceived by plant photoreceptors but also as an essential energy source captured by chloroplasts. However, excessive light can impose stress on plants. Fern gametophytes possess the unique ability to survive independently and play a critical role in the alternation of generations. Due to their predominantly shaded distribution under canopies, light availability becomes a limiting factor for gametophyte survival, making it imperative to investigate their response to light. Previous research on fern gametophytes’ light response has been limited to the physiological level. In this study, we examined the light response of Adiantum flabellulatum gametophytes under different photosynthetic photon flux density (PPFD) levels and identified their high sensitivity to low light. We thereby determined optimal and stress-inducing light conditions. By employing transcriptome sequencing, weighted gene co-expression network analysis, and Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses, we identified 10,995 differentially expressed genes (DEGs). Notably, 3 PHYBs and 5 Type 1 CRYs (CRY1s) were significantly down-regulated at low PPFD (0.1 μmol m-2 s-1). Furthermore, we annotated 927 DEGs to pathways related to photosynthesis and 210 to the flavonoid biosynthesis pathway involved in photoprotection. Additionally, we predicted 34 transcription factor families and identified a close correlation between mTERFs and photosynthesis, as well as a strong co-expression relationship between MYBs and bHLHs and genes encoding flavonoid synthesis enzymes. This comprehensive analysis enhances our understanding of the light response of fern gametophytes and provides novel insights into the mechanisms governing their responses to light.